The Anti-neuroinflammatory Activity of Tectorigenin Pretreatment via Downregulated NF-κB and ERK/JNK Pathways in BV-2 Microglial and Microglia Inactivation in Mice With Lipopolysaccharide - Lim, Hye-Sun; Kim, Yu Jin; Kim, Bu-Yeo; Park, Gunhyuk; Jeong, Soo-Jin (Frontiers in Pharmacology, 2018)
The activation of microglia is crucially associated with the neurodegeneration observed in many neuroinflammatory pathologies, such as multiple sclerosis, Parkinson’s disease, and Alzheimer’s disease. Tectorigenin (TEC) is an isoflavone isolated from various medicinal plants, such as Pueraria thunbergiana Benth, Belamcanda chinensis, and Iris unguicularis. In the present study, the neuroinflammatory effects of TEC were evaluated in both lipopolysaccharide (LPS)-treated BV-2 microglial and mouse models. TEC remarkably inhibited reactive oxygen species (ROS) generation. TEC also inhibits the production and expression of nitric oxide (NO), prostaglandin E2 (PGE2), tumor necrosis factor-a (TNF-a), and interleukin-6 (IL-6) in LPS-stimulated BV-2 cells. In addition, TEC suppressed the LPS-induced activation of nuclear factor-kB (NF-kB), phosphorylation of extracellular signal-regulated kinase (ERK), and c-Jun N-terminal kinase (JNK) to regulate the inflammatory mediators, such as inducible NO synthase (iNOS), cyclooxygenase-2 (COX-2), TNF-a, and IL-6. These results indicate that TEC may inhibit neuronal inflammation through the downregulation of inflammatory mediators, including iNOS, COX-2, TNF-a, and IL-6 by suppressing NF-kB/ERK/JNK-related signaling pathways. Furthermore, cotreatment with TEC and ERK inhibitor SCH772984 or JNK inhibitor SP600125 suppressed the overproduction of LPS-induced NO production in BV-2 cells. Consistent with the results of in vitro experiments, an LPS-induced brain inflammation mouse model, administration of TEC effectively decrease the levels of malondialdehyde, iNOS in hippocampus, and prevented increases in the levels of TNF-a and IL-6 in the serum. TEC showed marked attenuation of microglial activation. Finally, TEC inhibited protein expression of toll-like receptor 4 and myeloid differentiation factor 88 in LPS-activated BV-2 microglia and mouse models. Taken altogether, the cumulative findings suggested that TEC holds the potential to develop as a neuroprotective drug for the intervention of neuroinflammatory disorders.